Effects of different doses of oregano essential oil on growth performance, health parameters, and the gut microbiome-metabolome profile in heat-stressed Pinan cattle (Piedmontese × Nanyang) - Wang, Jiangge; Liu, Lei; Sheng, Jiashun; Zhang, Liyang; Li, Qiaozhen; Gao, Tengyun; Liu, Xian (Frontiers in Microbiology, 2026)
IntroductionThis study investigated the dose–response efficacy of dietary oregano essential oil (OEO) in mitigating severe heat stress (THI ≈ 86) in beef cattle.MethodsThirty-six Pinan bulls were fed a basal diet alone (control) or supplemented with 7 (L-OEO) or 14 g/d (H-OEO) of OEO for 60 days.ResultsThe low-dose OEO (7 g/d) significantly improved hepatic function (reduced ALT, AST; increased ALB, TP), enhanced immune (increased IgA, IgM) and antioxidant status (decreased MDA, increased SOD, CAT), and increased the ruminal abundance of Bacteroidota and Prevotella, which correlated negatively with acyl-glycine metabolites. In contrast, the high dose (14 g/d) only increased GSH-Px and T4, resulted in higher MDA than L-OEO, and did not significantly affect the rumen microbiota.ConclusionSupplementation with 7 g/d OEO optimally improved overall health and metabolic function in heat-stressed bulls, whereas a 14 g/d dose offered no additional benefits.